Efforts to Prevent Land Changes Due to Natural Disasters in Tridi Village Malang City - Afuw, Tanzizal; Koeswahyono, Imam; Masykur, Hamidi (IJBLE Scientific Publications Community Inc., 2024)
To ensure environmental sustainability and mitigate the risk of natural disasters such as flooding, the Malang City government has imposed a ban on residential development along the banks of the Brantas River through Malang City Regional Regulation No. 6 Year 2022. This study examines the measures adopted by the Malang City government to regulate the spatial layout of settlements in Kampung Tridi and prevent land degradation due to natural disasters, similar to the approach taken in Taman Bendung Tirto. Using Socio-Legal methodology, the study explores the perceptions and legal behaviors of riverside landowners and the government's strategies to protect the land. The findings of this study reveal that the Malang City government's efforts mainly focus on enforcing strict zoning in Kampung Tridi to comply with spatial regulations. This abstract is intended to provide a comprehensive overview of the study, highlighting the importance of the legal framework in urban planning and environmental protection